KONCEPCJA USTANOWIENIA RADY STANU (W ZWIąZKU Z PROJEKTEM RZECZNIKA PRAW OBYWATELSKICH JANUSZA KOCHANOWSKIEGO) - Krzymkowski, Marek (Zeszyty Prawnicze, 2016)
A PROPOSAL TO ESTABLISH A COUNCIL OF STATE IN POLAND Summary In 2006 Janusz Kochanowski, Poland’s Civil Rights Spokesman, put forward a proposal for the establishment of a council of state. The idea itself is not new, and goes back to the Napoleonic Conseil d’État. A council of state operated on Polish territories in the 19th century, when the country was partitioned and under foreign rule, during the brief spell under the Duchy of Warsaw controlled by Napoleonic France (1807-1815), and subsequently in the so-called Kingdom of Poland under Russian rule (1815-1831, 1833-1845, 1861-1867). Nowadays councils of state operate in France, Holland, Italy, and Belgium. Their primary tasks are judicial and consultative, as a supreme administrative court. Kochanowski’s proposal envisaged a council of state empowered to issue its opinion on prospective legislation at the draft bill stage. It was to have a president and a membership of 15 counsellors elected by Sejm for a 9-year term of office. Only candidates with the required juridical and/or academic qualifications would be eligible to stand for this office.